2015
DOI: 10.1186/s13287-015-0027-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel KCNQ1 mutation for type 1 long QT syndrome and assessment of the therapeutic potential of a novel IKs activator using patient-specific induced pluripotent stem cell-derived cardiomyocytes

Abstract: IntroductionType 1 long QT syndrome (LQT1) is a common type of cardiac channelopathy associated with loss-of-function mutations of KCNQ1. Currently there is a lack of drugs that target the defected slowly activating delayed rectifier potassium channel (IKs). With LQT1 patient-specific human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes (hiPSC-CMs), we tested the effects of a selective IKs activator ML277 on reversing the disease phenotypes.MethodsA LQT1 family with a novel heterozygous exon 7 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 26 publications
4
59
0
Order By: Relevance
“…The ion channel activator ML277 has been shown to augment specifically I Ks current and shorten the action potential duration in both healthy and LQT-CMs [46, 47]. Similarly, in this study, the ML277 shortened the cFPD although the effect was relatively mild in these hiPSC-CM clusters at 1-2 μM concentration.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The ion channel activator ML277 has been shown to augment specifically I Ks current and shorten the action potential duration in both healthy and LQT-CMs [46, 47]. Similarly, in this study, the ML277 shortened the cFPD although the effect was relatively mild in these hiPSC-CM clusters at 1-2 μM concentration.…”
Section: Discussionsupporting
confidence: 59%
“…For bisoprolol, 260 nM (upper limit of the therapeutic serum concentration) and 520 nM (twice the upper limit of the therapeutic concentration) concentrations were used. ML277 (I Ks channel activator) concentrations of 1 μM and 2 μM were chosen based on previous reports [46, 47]. The concentrations of I Ks blocker JNJ303 (300 nM and 1000 nM) were chosen based on our previous study [41].…”
Section: Methodsmentioning
confidence: 99%
“…The green area defines the normal QT interval range for humans. Data are shown as mean ± SD: 1, (Malan et al , 2016); 2, (Rocchetti/Sala et al , unpublished); 3, (Zhang et al , 2014); 4, (Zhang et al , 2014); 5, (Davis et al , 2012); 6, (Rocchetti/Sala et al , unpublished); 7, (Bellin et al , 2013); 8, (Sala et al , 2016); 9, (Bizy et al , 2013); 10, (Ma et al , 2013); 11, (Ma et al , 2015); 12, (Ma et al , 2015); 13, (Gibson et al , 2014a); 14, (Itzhaki et al , 2011); 15, (Gibson et al , 2014c); 16, (Lu et al , 2014); 17, (Gibson et al , 2014b); 18, (Mehta et al , 2014). (B) and (C) Composition of extracellular buffers (B) and pipette solutions (C) for current clamp experiments.…”
Section: Assays and Readoutsmentioning
confidence: 99%
“…Ma et al subsequently showed that hiPSC-CMs carrying a different KCNQ1 mutation (exon 7 del) not only faithfully recapitulated patients’ clinical phenotypes but also responded to ML277, a novel drug under development for arrhythmia suppression. 59 Egashira et al performed EP testing on hiPSC-CMs derived from a young survivor of sudden cardiac death (SCD) with clinical suspicion of LQT1. 58 They found a novel KCNQ1 mutation (1893delC) associated with a trafficking defect in Kv7.1 that was thought to be the culprit of the patient’s progressive clinical course.…”
Section: Disease Modeling Using Patient-specific Hipsc Derivativesmentioning
confidence: 99%